2006
DOI: 10.1007/s00467-006-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term renal function in heart transplant children on cyclosporine treatment

Abstract: Renal function deterioration is a reason of concern in heart transplantation. Our aim was to evaluate long-term renal function in heart transplant children on cyclosporine (CsA) treatment and to investigate the effect of several variables possibly involved in renal function deterioration. Creatinine clearances were retrospectively reviewed in 50 children (median follow 99.7 months after heart transplant). Gender, age, and body weight at transplant, rejection episodes, CsA cumulative dose, and trough levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For instance, Dello Strologo and Phan both reported mean cohort cGFR post‐transplant of approximately 100 mL/min/1.73 m 2 at 10 months and between one and four yr, respectively. Thus, even a 20 mL/min/1.73 m 2 overestimation would place the GFR mean for the entire cohort near 80 mL/min/1.73 m 2 , the authors’ cut‐off for renal insufficiency in both studies (11, 17).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For instance, Dello Strologo and Phan both reported mean cohort cGFR post‐transplant of approximately 100 mL/min/1.73 m 2 at 10 months and between one and four yr, respectively. Thus, even a 20 mL/min/1.73 m 2 overestimation would place the GFR mean for the entire cohort near 80 mL/min/1.73 m 2 , the authors’ cut‐off for renal insufficiency in both studies (11, 17).…”
Section: Discussionmentioning
confidence: 94%
“…While the overestimation of renal function by the cGFR based on creatinine clearance has already been reported (15), this study also found that on a cohort‐wide basis, relying solely on cGFR could greatly underestimated the burden of renal disease following pediatric transplantation. Most pediatric heart transplantation studies looking at renal insufficiency have used estimated GFR calculated with the Schwartz formula (9, 11, 13, 14, 16, 17). While it is impossible to predict the extent to which the use of cGFR overestimated GFR in other patient populations, our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some survivors develop end-stage renal disease (ESRD), requiring renal replacement therapy, either with dialysis or renal Tx. 1,2,8 A recent analysis of national transplant data estimated that, after pediatric heart Tx, the 10-year actuarial risks for development of ESRD and chronic renal insufficiency (CRI) were 4.3% and 11.8%, respectively. 9 Furthermore, development of renal impairment was shown to be associated with a 9-fold increased risk of mortality.…”
mentioning
confidence: 99%
“…[1][2][3][4] After the advent of cyclosporine in the 1980s, survival rates after pediatric heart transplantation (Tx) have been improving steadily. [5][6][7] With improving long-term survival after pediatric heart Tx, renal dysfunction is gaining increased attention.…”
mentioning
confidence: 99%